The Comparison of Postoperative Outcomes Open and Closed Reduction for Patellar Fractures - Lee, Si Young; Choi, Jun Young; Lee, Hyun Il; Lee, Jung Min; Cho, Jin Ho (The Journal of Knee Surgery, 2020)
Patellar fractures account for approximately 1% of all human body fractures. This study aimed to compare the surgical outcomes of open reduction and closed reduction for patellar fractures. This retrospective study included 62 patients (63 cases) who underwent surgical treatment of patellar fractures from 2008 to 2013. Of the 63 cases, open and closed reductions were performed in 42 and 21 cases, respectively. Plain radiography was used to assess fracture healing. Comminuted patellar fracture was the most common fracture type in both groups. Tension band wiring and cannulated screw fixation were mainly used in the open and closed reduction groups, respectively. There was no significant difference in the modified hospital for special surgery score, visual analog scale score for pain, and range of motion between the two groups. The mean union time was 3.2 and 3.0 months in open and closed reductions, respectively. Postoperative knee stiffness was noted in five cases of open reduction and in three cases of closed reduction. One patient in the open reduction group had a refracture. There were no notable differences in treatment outcomes between open and closed reductions. Thus, closed reduction may not be inferior to open reduction as a surgical treatment for patellar fractures.
Keywords: patellar fractures; classification; surgical outcome; open reduction; closed reduction